Transcriptome Analysis Revealed Inflammation Is Involved in the Impairment of Human Umbilical Vein Endothelial Cells Induced by Post-hemorrhagic Shock Mesenteric Lymph - Wang, Qi; Chi, Zhen-Fen; Wei, Di; Zhao, Zhen-Ao; Zhang, Hong; Zhang, Li-Min; Liu, Yan-Xu; Kang, An-Ling; Zhao, Meng; Wang, Peng; Nie, Ling-Hu; Niu, Chun-Yu; et al. (Frontiers in Immunology, 2020)
Vascular endothelial injury caused by post-hemorrhagic shock mesenteric lymph (PHSML) return is an important manifestation during refractory hemorrhagic shock. By using human umbilical vein endothelial cells (HUVECs) and transcriptome analysis, the present study sought to investigate the molecular mechanism underlying adverse effect of PHSML on vascular endothelium. PHSML was collected from male rats underwent hemorrhagic shock and following resuscitation, while normal mesenteric lymph (NML) was harvested from the sham rats. HUVECs were incubated with the culture medium containing either 10% phosphate buffered saline (Control), NML or PHSML for three hours, and then were harvested for RNA sequencing (RNA-seq). In comparison with NML treated cells, 37 genes were differentially expressed in PHSML-treated HUVECs, including 32 upregulated genes and 5 downregulated genes. These differentially expressed genes were mainly enriched in inflammatory pathways, including signaling pathways for activation of NOD-like receptor, NF-κB and TNF. Furthermore, we found C-C motif chemokine ligand 2 (CCL2) was increased significantly after PHSML treatment, and Bindarit, a CCL2 production inhibitor, attenuated the damage of HUVECs induced by PHSML. The results provide molecular evidence on vascular endothelium damage caused by PHSML. CCL2 might represent a new target for reducing the vascular injury after severe hemorrhagic shock.